Strategies for Building Student Engagement in Online Learning in Indonesia through Self-Determination Theory - Diah Pranitasari; Iman Sofian Suriawinata; Dodi Prastuti; Pristina Hermastuti; Enung S Saodah (Monas: Jurnal Inovasi Aparatur, 2025)
This study aims to analyze the influence of intrinsic motivation on students’ digital readiness in the post-pandemic era using the framework of Self-Determination Theory (SDT). The research employed a quantitative approach with a descriptive-verificative survey method. The respondents consisted of 230 undergraduate students from various public and private universities in Indonesia who had participated in online and hybrid learning. Data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software.  The results indicate that intrinsic motivation has a significant effect on students’ digital readiness (R² = 0.62). All three SDT dimensions—competence, autonomy, and relatedness—positively influence digital readiness, with competence showing the strongest effect (β = 0.39), followed by autonomy (β = 0.27) and relatedness (β = 0.21). These findings emphasize that students’ digital readiness is shaped not only by technical skills but also by psychological factors related to intrinsic motivation.